TAXES AND CAPITAL STRUCTURE OF MANUFACTURING COMPANIES IN INDONESIA - Nurlita Sukma Alfandia (Universitas Airlangga, 2018)
Companies have a tendency to use debt as a source of funding to minimize the tax payable. This study aims to determine the effect of taxes on the company's debt policy. The tax variable is proxied into profit after tax, effective tax rate, and marginal tax rate. Meanwhile, the variable of debt policy is proxied to be the ratio of debt to capital. The research sample used is a manufacturing company listed on the Indonesia Stock Exchange and has audited financial statements for 2012-2016. In addition, the company does not have a negative capital balance (capital deficiency) and suffers a fiscal loss, and is required to provide the necessary information in the study. The selected sample amounted to 135 companies. This study uses simple regression analysis with three regression models made. Based on the tests conducted, it is known that the Earning After Tax (EAT) and Effective Tax Rate (ETR) variables can affect the company's debt policy. Meanwhile, the Marginal Tax Rate (MTR) does not affect the company's debt policy. Further research is suggested to use other alternatives in measuring ETR and MTR variables. In addition, it is hoped that the next research will consider other types of businesses as research samples.